Potential Mechanisms of Transmission of Tick-Borne Viruses at the Virus-Tick Interface - Maqbool, Mahvish; Sajid, Muhammad Sohail; Saqib, Muhammad; Anjum, Faisal Rasheed; Tayyab, Muhammad Haleem; Rizwan, Hafiz Muhammad; Rashid, Muhammad Imran; Rashid, Imaad; Iqbal, Asif; Siddique, Rao Muhammad; Shamim, Asim; Hassan, Muhammad Adeel; et al. (Frontiers in Microbiology, 2022)
Ticks (Acari; Ixodidae) are the second most important vector for the transmission of pathogens to humans, livestock, and wildlife. Tick-borne viruses (TBVs) belong from two orders (Bunyavirales and Mononegavirales) containing nine families (Bunyaviridae, Rhabdoviridae, Asfarviridae, Orthomyxovirida, Reoviridae, Flaviviridae, Phenuviridae, Nyamiviridae and Nairoviridae). About 38 viral species are being transmitted by less than 10% of the tick species (of the family Ixodidae and Argasidae). Tick-borne viral diseases have also been classified as an emerging threat to public health and animals. Tick-host interaction plays an important role in the successful transmission of pathogens. Ticks’ salivary glands are the main cellular machinery involved in the update, settlement, and multiplication of the viruses. Further, tick saliva also participates as an augmenting tool during this physiological process for transmission. Tick saliva is an important key player in the successful transmission of pathogen and contains different antimicrobial proteins e.g. defensin, serine, proteases, and cement protein which are a key player in tick-virus interaction. Besides, some other immunological factors e.g. toll like receptors, scavenger receptors, Janus-kinase (JAK-STAT) pathway, and immunodeficiency pathway (IMD) are involved in tick-virus interaction by helping in virus assembly and increase in transmission. This review would probably be a maiden attempt to comprehensively elaborate the epidemiological determinants of TBVs with a focus on the intra-vector physiological processes involved in the successful execution of the docking, uptake, settlement, replication, and transmission processes of the arboviruses. This would add up valuable data into the existing bank of knowledge for the global stakeholder, policymakers, and scientific community